The Impact of Perceived Risk and Perceived Ease of use on Purchase Intention Through Satisfaction of Tokopedia Application Consumers - Nardi; Muhammad Amir Ariandi; Askiah (Jurnal Ekonomi dan Manajemen, 2025)
In the current landscape, online shopping offers unparalleled convenience to consumers, allowing them to purchase from the comfort of their homes. As a result, many users prioritize security and ease of use when choosing an online shopping platform. Ensuring secure transactions and user-friendly interfaces have become essential for e-commerce platforms to meet consumer expectations. This study aims to provide insights for e-commerce platforms, particularly the Tokopedia app, regarding factors that influence consumer purchase intentions, namely perceived risk as well as ease of use mediated by consumer satisfaction. A total of 200 participants selected through purposive sampling based on accidental random sampling, who use the Tokopedia application, were included in this study. Data were processed using Partial Least Squares (PLS) 4, and five hypotheses were proposed. The findings showed that all hypotheses were supported. These results suggest that Tokopedia should improve its security measures and continue to innovate to ensure ease of use for consumers. Prior studies provide support for these findings.